استخدام مواقع التواصل الاجتماعي وأثره على التكيف المدرسي لدى تلاميذ الطور الثانوي دراسة ميدانية على عينة من مستخدمي الفايسبوك بثانويات الوادي، توقرت، ورقلة. - شباط صابر (université d'eloud, 2026)
تهدف الدراسة إلى التعرف على أثر استخدام مواقع التواصل الاجتماعي على التكيف المدرسي لدى تلاميذ ثانويات الجنوب الجزائري، من خلال تحليل أنماط الاستخدام ودوافعه والإشباعات المتحققة منه، وربطها بأبعاد التكيف المدرسي المتمثلة في العلاقة بالزملاء والأساتذة، والتحصيل والتوافق مع المنهاج، والاتجاه نحو المدرسة ومحيطها. اعتمد الباحث المنهج المسحي الارتباطي، وطبقت الدراسة على عينة غير احتمالية قوامها (508) تلميذا وتلميذة من (11) ثانوية بولايتي الوادي وتوقرت خلال الموسم الدراسي 2024/2025، باستخدام استبانة مكونة من (75) بندا، شملت مقياسا لاستخدامات مواقع التواصل الاجتماعي من إعداد الباحث، ومقياس التكيف المدرسي المعدل لمحمود الزيادي، وقد أظهرت الأداة درجة ثبات مرتفعة (Cronbach’s Alpha = 0.87)، وتم تحليل البيانات باستخدام برنامج SPSS. أظهرت النتائج أن أغلب التلاميذ يستخدمون مواقع التواصل الاجتماعي بشكل مكثف ولكن في حدود زمنية مضبوطة نسبيًا، مع تفضيل فترات العطل وأوقات الفراغ. كما تنوعت أنشطتهم بين المتابعة والتفاعل والنشر، مع استخدام متوسط في المجال الدراسي، وبرزت الدوافع الإيجابية للاستخدام بدرجة مرتفعة، مقابل انخفاض الدوافع السلبية رغم وجود نسب محدودة لاستخدامات غير تربوية أو هروبية. كما بينت الدراسة أن استخدام مواقع التواصل الاجتماعي يسهم في إشباع عدة حاجات لدى التلاميذ، خاصة الترفيه، ويرتبط بارتفاع مستوى التكيف المدرسي لديهم، لاسيما في بعدي العلاقة بالأساتذة والعلاقة بالزملاء، ما يشير إلى وجود علاقة إيجابية بين بعض أنماط ودوافع الاستخدام ومستوى التكيف المدرسي This study examines the correlational relationship between social networking site use and school adjustment among high school students in southern Algeria. It focuses on how patterns, motivations, and gratifications of social media use relate to school adjustment dimensions: relationships with teachers and peers, academic achievement and curriculum adaptation, and attitudes toward school and its environment. Using a correlational survey method, data were collected from a non-probability sample of 508 students from 11 high schools in El Oued and Touggourt during the 2024/2025 academic year. A 75-item questionnaire was employed, including a researcher-designed Social Media Use Scale and an adapted School Adjustment Scale by Mahmoud Al-Ziyadi. Statistical analysis via SPSS confirmed strong validity and reliability (Cronbach’s Alpha = 0.87). Findings indicate that most students use social media intensively but in a relatively controlled manner, typically spending 2–3 hours daily, with peak use during weekends and school breaks. Their activities are diverse and active, while educational use remains moderate. Positive motivations for use—such as entertainment, self-expression, social interaction, and learning—were high, whereas negative motivations were generally low despite notable minorities engaging in inappropriate or escapist use. Social media use primarily fulfills entertainment needs. Overall, students demonstrated a high level of school adjustment, particularly in their relationships with teachers and academic adaptation. Statistical analyses revealed significant correlations: patterns of use, positive motivations, and gratifications were positively associated with higher school adjustment, while negative motivations were inversely related to school adjustment across all dimensions.
أطروحة دكتوراء
Keywords: أثر; الاستخدام; التواصل الاجتماعي; التكيف المدرسي; تلاميذ; الطور الثانوي; الجنوب الجزائري